A comprehensive review on power quality issues and disturbances mitigation through shunt active power filters - Chauhan, Siddharthsingh K.; Chauhan, Vineeta S. (Institute of Advanced Engineering and Science, 2024)
In contemporary power systems, power quality (PQ) has become a matter of paramount concern. The challenges associated with PQ extend beyond conventional three-phase systems, encompassing the integration of various distributed generation (DG) sources like renewable energy installations, storage systems, and diverse power generation technologies such as diesel generators and fuel cells. The prevalent adoption of rapid-switching devices within the utility infrastructure has resulted in a surge of harmonics and reactive power disturbances. The increased use of harmonics-producing loads has led to several power quality issues, particularly harmonics. The distortions caused by these power quality issues must adhere to the limits established by international standards. Mitigation of these concerns is critical, and active power filters are a realistic option. However, passive filters have problems such as bulkiness, and resonance with either/both load and utility impedance, and the source impedance affects filtering properties. As a result, active power filters (APF) are designed to address the shortcomings of passive filters. Active power filters (APF) offer several advantages over passive filters, including compact size, enhanced filtering characteristics, dynamic performance, and flexible operation. The control strategy of APF strongly influences the APF performance, efficiency, and reliability. This paper presents a detailed assessment of current active filter control systems, highlighting their key features. The characteristics, performance, applicability, and implementation of various control techniques are explored and investigated.